FAITH FORMATION IN A MULTI-RELIGIOUS CONTEXT - Anand, Subhash (Asian Horizons, 2020)
Life is shaped from within and also by the environment. What plant or tree a seed will be and the suitable environment it needs is determined from within. This is also true for the teaching-learning process that aims to promote human growth. An effective pedagogy is guided by a certain vision, a frame of mind, a set of foundational ideas and principles. We are clear as to what we want to achieve through our teaching.